2020
DOI: 10.18267/j.cebr.250
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Business Risks by SMEs in the Czech Republic

Abstract: This article aims to find out which business risks determine the perception of the business environment of small and medium-sized enterprises (SME) in the future. 454 SMEs from the Czech Republic participated in the case study by filling in an online questionnaire. Linear regression models were used to verify statistically significant causal relationships between selected indicators of business risks and respondents' perception of the future of business. The results show that selected indicators of the market,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Next, the relevance of this issue in Central Europe is further supported by poor performance of the countries in the region in the 'Second chance' policy dimension of the EU's Small Business Act (European Commission, 2019) (with Slovakia performing the worst in the region), which makes the entrepreneurial failure even more sensitive issue, due to its problematic resolving. In addition, a study by Dvorsky et al (2020) indicated that perception of business risk (in this case, among the Czech SMEs) is related to perceived expectations related to a business's future. In fact, Szerb et al (2017) identified risk perception as the main bottleneck pillar of the Czech entrepreneurial ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the relevance of this issue in Central Europe is further supported by poor performance of the countries in the region in the 'Second chance' policy dimension of the EU's Small Business Act (European Commission, 2019) (with Slovakia performing the worst in the region), which makes the entrepreneurial failure even more sensitive issue, due to its problematic resolving. In addition, a study by Dvorsky et al (2020) indicated that perception of business risk (in this case, among the Czech SMEs) is related to perceived expectations related to a business's future. In fact, Szerb et al (2017) identified risk perception as the main bottleneck pillar of the Czech entrepreneurial ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable, however, that prior studies have largely overlooked the influence of the psychological factors associated with SME owners/managers on their decisions to utilize external finance. The subjective factors influencing the behavior of SME owners/managers toward external finance warrant consideration (Dvorský et al 2020). It is argued that it is crucial to understand risk perception, as it shapes the type and magnitude of responses to risks (Le and Arcodia 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to solve this problem is controlling, which is an effective tool for active management of the future of the company, which aims to provide real information in real-time to increase the performance and financial health of the company (Bernardová et al, 2020;Dvorský et al, 2020;Lesnikova & Schmidtova, 2020;Hitka et al, 2014;Stroková & Drábek, 2018;Vetráková et al, 2018). At present, it is not possible to implement controlling without adequate software support.…”
Section: Introductionmentioning
confidence: 99%